Cost-effectiveness analysis of Tumor Treating Fields treatment in Chinese patients with metastatic non-small cell lung cancer - Pei, Zhengda; Xiao, Ningping; Yang, Pei (Frontiers in Public Health, 2024)
Background: The LUNAR trial demonstrated the significant efficacy and safety of Tumor Treating Fields (TTFields) plus standard-of-care (SOC) (immune checkpoint inhibitor [ICI] and docetaxel [DTX]) for patients with previously treated metastatic non-small cell lung cancer (mNSCLC). However, it remains uncertain as to whether the high costs are justified by the corresponding survival benefits. Here, the cost-effectiveness of using TTFields plus SOC for treating mNSCLC was evaluated from the perspective of the Chinese healthcare system. Methods: A Markov model with a 15-year time horizon was established and used to comparedeveloped to enable the simulation of treatment-associated costs and patient outcomes when comparing TTFields plus SOC to SOC alone. Primary outcomes for these analyses included total costs, life-years (LYs), quality-adjusted LYs (QALYs), and incremental cost-effectiveness ratio (ICER) values. The impact of paramere uncertainty on model outcomes was evaluated through sensitivity analyses. Additional subgroup and scenario analyses were also performed to extend these results. Results: While TTFields plus SOC exhibited a 74,688 increase in total costs relative to SOC (96,092 vs. 21,404), it was associated with 0.38 additional QALYs (1.08 vs. 0.82 QALYs) for an ICER of 284,490/QALY. This value exceeded the 35,983/QALY willingness-to-pay (WTP) threshold selected for these analyses by a wide margin. Relative to ICI and DTX treatment, the incremental costs of TTFields plus ICI and TTFields plus DTX were 78,115 and 71,307, respectively, with corresponding gains of 0.42 and 0.13 QALYs, yielding ICERs of 187,434/QALY, and 546,386/QALY. The parameter that most strongly impacted the results of these analyses was the cost of TTFields. Conclusions: The results indicated that given current treatment costs, TTFields plus SOC was insufficiently cost-effective in treating patients with mNSCLC in China, although TTFields plus ICI yields substantial health benefits.